Hot-rolled steel sheet

By controlling the original austenite grain and temperature history, reducing the area ratio of the new martensite and residual austenite aggregates, optimizing the chemical composition and metal structure of the hot-rolled steel plate, the strength and strength of the hot-rolled steel plate are solved. The hydrogen embrittlement resistance characteristics problem has achieved high strength, ductility and pore reaming hot-rolled steel plates.

CN119137299AInactive Publication Date: 2024-12-13NIPPON STEEL CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037700.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-07
Filing Date
2023-06-23
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While reducing the thickness of the existing hot-rolled steel plates, it is difficult to ensure static breaking strength and yield strength at the same time. Especially in automobile walking parts, the hydrogen embrittlement resistance at the cut-off end surface has not been effectively considered.

Method used

By controlling the particle size and shape of the original austenite grains, strictly controlling the temperature history after the winding process, and reducing the area ratio of the aggregates of new martensite and residual austenite with a length of more than 30 μm, the steel plate is optimized. chemical composition and metal structure.

Benefits of technology

Hot-rolled steel plates with high strength, excellent ductility, pore reaming and hydrogen embrittlement resistance are suitable for automobile walking parts and improve the overall performance of the parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112050290000261
    Figure BDA0005112050290000261
  • Figure BDA0005112050290000271
    Figure BDA0005112050290000271
  • Figure BDA0005112050290000281
    Figure BDA0005112050290000281
Patent Text Reader

Abstract

This hot-rolled steel sheet has a desired chemical composition, and has a metallographic structure comprising, in area%, 10% or more of bainite, 10% or more of tempered martensite, 70-96% of the total of bainite and tempered martensite, 20% or less of new martensite, 4-12% of retained austenite, 5% or less of ferrite, and 5% or less of pearlite. The average grain diameter of prior austenite grains is 20.0 [mu] m or less, the average aspect ratio of prior austenite grains is 3.00 or less, and the area ratio of aggregates of new martensite and retained austenite having a major diameter of 30 [mu] m or more is 5% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to hot rolled steel sheets.

[0002] This application claims priority based on Japanese Patent Application No. 2022-109509 filed in Japan on July 7, 2022, and the contents of which are incorporated herein by reference. Background Art

[0003] In recent years, progress has been made in the lightweighting of automobile and mechanical parts. The lightweighting of automobile and mechanical parts can be achieved by designing the shape of the parts to the optimal shape to ensure rigidity. Furthermore, for blank formed parts such as press-formed parts, the weight can be reduced by reducing the plate thickness of the part material.

[0004] However, in order to reduce the plate thickness while ensuring the strength characteristics of the components such as static fracture strength and yield strength, it becomes necessary to use high-strength materials. In particular, in automotive running parts such as lower arms, connecting rods and steering knuckles, the application of steel plates with a grade exceeding 780MPa has begun to be studied. These automotive running parts are manufactured by flanging, stretching flanges and bending the steel plates. Therefore, the steel plates used in these automotive running parts are required to have excellent formability, especially ductility and hole expansion.

[0005] For example, Patent Document 1 discloses a high-strength steel plate having a strength of more than 700 MPa, characterized in that the ratio of the amount of C in atomic % to the total amount of Mo and Ti, i.e., C / (Mo+Ti), is 0.5 to 3.0, the metal structure is a two-phase structure of ferrite and bainite, and carbides containing Ti and Mo are dispersed and precipitated in the ferrite phase.

[0006] Patent Document 2 discloses a high-strength hot-rolled steel sheet having low anisotropy of stretch flangeability, wherein 88% or more of the steel structure contains a bainite structure.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent No. 3891030

[0010] Patent Document 2: Japanese Patent No. 3197571 Summary of the invention

[0011] Problems to be solved by the invention

[0012] In order to further improve the strength for the purpose of thinning the wall of the parts, a hot rolled steel sheet with a high C content and containing retained austenite is sometimes used. In such a hot rolled steel sheet, hydrogen embrittlement cracking is easily generated at the cut end surface, and the hydrogen embrittlement resistance may be deteriorated.

[0013] In the above-mentioned Patent Documents 1 and 2, the strength must be further improved, and no consideration is given to the hydrogen embrittlement resistance of the cut end surface.

[0014] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a hot-rolled steel sheet having high strength and excellent ductility, hole expandability, and hydrogen embrittlement resistance.

[0015] Means for solving problems

[0016] The present inventors have conducted in-depth research on methods for improving the hydrogen embrittlement resistance of the cut end surface of a hot-rolled steel sheet. As a result, they have found that the hydrogen embrittlement resistance of the cut end surface of the hot-rolled steel sheet can be improved by reducing the area ratio of the aggregate of fresh martensite and retained austenite with a long diameter of 30 μm or more.

[0017] The present inventors have found that, in order to produce the hot-rolled steel sheet, it is effective to control the grain size and shape of prior austenite grains in the rough rolling process and the finish rolling process and to strictly control the temperature history after the coiling process.

[0018] The gist of the present invention made based on the above findings is as follows.

[0019] (1) The chemical composition of the hot-rolled steel sheet according to one embodiment of the present invention contains, in terms of mass %, the following:

[0020] C: 0.13~0.23%

[0021] Si: 0.70-1.79%,

[0022] Mn: 1.79-3.00%,

[0023] P: 0.060% or less,

[0024] S: 0.005% or less,

[0025] N: 0.0070% or less,

[0026] O: 0.010% or less,

[0027] Al: 0.010~0.430%,

[0028] Ti: 0.006~0.055%,

[0029] Nb: 0.005-0.040%,

[0030] B: 0.0001~0.0030%,

[0031] Cr: 0~0.660%,

[0032] Mo: 0~0.300%,

[0033] Cu: 0~1.000%,

[0034] Ni: 0~1.000%,

[0035] Sn: 0~0.100%,

[0036] Ca: 0~0.0200%,

[0037] As: 0~0.100%,

[0038] Bi: 0~0.020%,

[0039] Mg: 0~0.0200%,

[0040] Zr: 0~0.400%,

[0041] V: 0~0.200%、

[0042] REM: 0~0.1000%、

[0043] Co: 0~0.2000%,

[0044] W: 0~0.2000% and

[0045] Zn: 0~0.2000%,

[0046] The rest contains Fe and impurities.

[0047] In metal structures, expressed as area %,

[0048] Bainite: more than 10%,

[0049] Tempered martensite: more than 10%,

[0050] Total of bainite and tempered martensite: 70-96%,

[0051] New martensite: less than 20%,

[0052] Retained austenite: 4-12%,

[0053] Ferrite: less than 5%,

[0054] Pearlite: less than 5%,

[0055] The average grain size of the original austenite grains: 20.0 μm or less,

[0056] The average aspect ratio of the original austenite grains: less than 3.00,

[0057] The area ratio of the aggregate of fresh martensite and retained austenite having a major diameter of 30 μm or more is 5% or less.

[0058] (2) According to the hot-rolled steel sheet described in (1) above, the pearlite in the metal structure may be less than 3%.

[0059] (3) According to the hot-rolled steel sheet described in (1) or (2), the region where the average value of the nanoindentation hardness of the bainite at a load of 5000 μN and a load speed of 500 μN / s is 4.7 GPa or less is 30% or less.

[0060] (4) In the hot-rolled steel sheet according to any one of (1) to (3), the chemical composition may contain, in terms of mass %, one or more of the following elements:

[0061] Cr: 0.020~0.660%,

[0062] Mo: 0.001~0.300%,

[0063] Cu: 0.001~1.000%,

[0064] Ni: 0.001~1.000%,

[0065] Sn: 0.001~0.100%,

[0066] Ca: 0.0005~0.0200%,

[0067] As: 0.001~0.100%,

[0068] Bi: 0.001~0.020%,

[0069] Mg: 0.0005~0.0200%,

[0070] Zr: 0.001~0.400%,

[0071] V: 0.001~0.200%,

[0072] REM: 0.0005~0.1000%、

[0073] Co: 0.0005~0.2000%,

[0074] W: 0.0005~0.2000% and

[0075] Zn: 0.0005~0.2000%.

[0076] Effects of the Invention

[0077] According to the above aspects of the present invention, it is possible to provide a hot-rolled steel sheet having high strength and excellent ductility, hole expandability, and hydrogen embrittlement resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 This is a diagram for explaining a method of approximating a crystal grain with an ellipsoid. DETAILED DESCRIPTION

[0079] Hereinafter, the hot-rolled steel sheet of the present embodiment will be described in detail. However, the present invention is not limited to the configuration disclosed in the present embodiment, and various modifications can be made without departing from the gist of the present invention.

[0080] For the numerical ranges described below with "to", the lower limit and upper limit are included in the range. For the numerical values ​​expressed as "lower than" or "exceeding", the values ​​are not included in the numerical range. All "%" about chemical composition means "mass %".

[0081] The chemical composition of the hot-rolled steel sheet according to the present embodiment includes, by mass%, C: 0.13-0.23%, Si: 0.70-1.79%, Mn: 1.79-3.00%, P: 0.060% or less, S: 0.005% or less, N: 0.0070% or less, O: 0.010% or less, Al: 0.010-0.430%, Ti: 0.006-0.055%, Nb: 0.005-0.040%, B: 0.0001-0.0030%, and the remainder: Fe and impurities.

[0082] Hereinafter, each element will be described in detail.

[0083] C: 0.13~0.23%

[0084] C is an element that improves the tensile strength of hot-rolled steel sheets. If the C content is less than 0.13%, the area ratio of ferrite becomes too high, and the desired tensile strength cannot be obtained in the hot-rolled steel sheet. Therefore, the C content is set to 0.13% or more. The C content is preferably 0.14% or more, and more preferably 0.16% or more.

[0085] On the other hand, when the C content exceeds 0.23%, the area ratio of fresh martensite becomes too high, and the hole expansion property and hydrogen embrittlement resistance of the hot-rolled steel sheet deteriorate. Therefore, the C content is set to 0.23% or less. The C content is preferably 0.21% or less, and more preferably 0.20% or less.

[0086] Si: 0.70~1.79%

[0087] Si is an element that stabilizes retained austenite. When the Si content is less than 0.70%, the desired amount of retained austenite cannot be obtained, and the ductility of the hot-rolled steel sheet deteriorates. Therefore, the Si content is set to 0.70% or more. The Si content is preferably 0.90% or more, and more preferably 1.00% or more.

[0088] On the other hand, if the Si content exceeds 1.79%, the area ratio of retained austenite becomes too high, and the hole expandability of the hot-rolled steel sheet deteriorates. Therefore, the Si content is set to 1.79% or less. The Si content is preferably 1.60% or less, more preferably 1.40% or less, and even more preferably 1.30% or less.

[0089] Mn: 1.79~3.00%

[0090] Mn is an element required to improve the strength of hot-rolled steel sheets. If the Mn content is less than 1.79%, the area ratio of ferrite becomes too high and the desired tensile strength cannot be obtained. Therefore, the Mn content is set to 1.79% or more. The Mn content is preferably 2.00% or more, and more preferably 2.20% or more.

[0091] On the other hand, if the Mn content exceeds 3.00%, the ductility of the hot-rolled steel sheet deteriorates. Therefore, the Mn content is set to 3.00% or less. The Mn content is preferably 2.60% or less, and more preferably 2.40% or less.

[0092] P: 0.060% or less

[0093] P is an element segregated in the center of the plate thickness of the hot rolled steel plate. In addition, P is also an element that makes the weld embrittled. If the P content exceeds 0.060%, it becomes easy to cause slab cracking and becomes difficult to cast. Therefore, the P content is set to 0.060% or less. The P content is preferably 0.020% or less, and more preferably 0.015% or less.

[0094] The lower the P content, the better, and preferably 0%. However, if the P content is reduced excessively, the P removal cost increases significantly, so the P content may be set to 0.001% or more.

[0095] S: 0.005% or less

[0096] S is an element that makes the slab embrittled by existing as sulfide in steel. In addition, S is also an element that deteriorates the formability of hot-rolled steel sheets. If the S content exceeds 0.005%, the hole expansion of the hot-rolled steel sheet deteriorates. Therefore, the S content is set to 0.005% or less. The S content is preferably 0.004% or less, and more preferably 0.003% or less.

[0097] The lower the S content, the more preferable it is, and preferably 0%. However, if the S content is reduced excessively, the S removal cost increases significantly, so the S content may be set to 0.001% or more.

[0098] N: 0.0070% or less

[0099] N is an element that forms coarse nitrides in steel and makes the slab embrittled. If the N content exceeds 0.0070%, the risk of slab cracking increases significantly. Therefore, the N content is set to 0.0070% or less. The N content is preferably 0.0050% or less, and more preferably 0.0035% or less.

[0100] The lower the N content, the more preferable it is, and preferably 0%. However, if the N content is reduced excessively, the cost of removing N will increase significantly, so the N content may be set to 0.0005% or more.

[0101] O: 0.010% or less

[0102] If O is contained in steel in large amounts, it forms coarse oxides that become the starting point of fracture, and deteriorates the hydrogen embrittlement resistance of the hot-rolled steel sheet. Therefore, the O content is set to 0.010% or less. The O content is preferably 0.008% or less, and more preferably 0.006% or less.

[0103] In order to disperse a large amount of fine oxides during deoxidation of molten steel, the O content may be set to 0.001% or more.

[0104] Al: 0.010~0.430%

[0105] Al is an element that acts as a deoxidizer and improves the cleanliness of steel. If the Al content is less than 0.010%, sufficient deoxidation effect cannot be obtained, and a large amount of inclusions (oxides) are formed in the steel plate. Such inclusions deteriorate the hole expandability of the hot-rolled steel plate. Therefore, the Al content is set to 0.010% or more. The Al content is preferably 0.040% or more, and more preferably 0.100% or more.

[0106] On the other hand, when the Al content exceeds 0.430%, slab cracking tends to occur, and casting becomes difficult. Therefore, the Al content is set to 0.430% or less. The Al content is preferably 0.400% or less, 0.350% or less, and more preferably 0.200% or less.

[0107] Ti: 0.006~0.055%

[0108] Ti is an element that increases the strength of hot-rolled steel sheets by forming fine nitrides in steel. If the Ti content is less than 0.006%, the desired tensile strength cannot be obtained in the hot-rolled steel sheet. Therefore, the Ti content is set to 0.006% or more. The Ti content is preferably 0.010% or more, and more preferably 0.020% or more.

[0109] On the other hand, if the Ti content exceeds 0.055%, the risk of slab cracking increases significantly. Therefore, the Ti content is set to 0.055% or less. The Ti content is preferably 0.040% or less, and more preferably 0.030% or less.

[0110] Nb: 0.005~0.040%

[0111] Nb is an element that suppresses abnormal grain growth of austenite grains during hot rolling. In addition, Nb is also an element that increases the strength of hot-rolled steel sheets by forming fine carbides. If the Nb content is less than 0.005%, the original austenite grains cannot be refined, and the area ratio of the aggregate of new martensite and retained austenite with a long diameter of more than 30 μm becomes high, and the hole expansion and hydrogen embrittlement resistance of the hot-rolled steel sheet deteriorate. Therefore, the Nb content is set to 0.005% or more. The Nb content is preferably 0.010% or more, and more preferably 0.020% or more.

[0112] On the other hand, if the Nb content exceeds 0.040%, the aspect ratio of the original austenite grains increases, and the area ratio of the aggregate of the newly formed martensite and the retained austenite with a long diameter of 30 μm or more increases, and the hole expansion and hydrogen embrittlement resistance of the hot-rolled steel sheet deteriorate. Therefore, the Nb content is set to 0.040% or less. The Nb content is preferably 0.030% or less.

[0113] B: 0.0001~0.0030%

[0114] B is an element that improves the strength of the hot-rolled steel sheet by suppressing the formation of ferrite in the cooling process. If the B content is less than 0.0001%, the desired tensile strength cannot be obtained in the hot-rolled steel sheet. Therefore, the B content is set to 0.0001% or more. The B content is preferably 0.0005% or more, and more preferably 0.0010% or more.

[0115] On the other hand, if the B content exceeds 0.0030%, the hot deformation resistance increases and hot rolling becomes difficult. Therefore, the B content is set to 0.0030% or less. The B content is preferably 0.0025% or less.

[0116] The remainder of the chemical composition of the hot-rolled steel sheet of the present embodiment may also be Fe and impurities. In the present embodiment, the so-called impurities refer to elements mixed from ore, scrap iron, or the manufacturing environment as raw materials, or elements allowed within a range that does not adversely affect the characteristics of the hot-rolled steel sheet of the present embodiment.

[0117] The hot-rolled steel sheet of the present embodiment may contain the following optional elements in place of a portion of Fe. When the optional elements are not contained, the lower limit of the content is 0%. Each optional element will be described below.

[0118] Cr: 0.020~0.660%

[0119] Cr is an element that reduces the amount of ferrite and increases the strength of the hot-rolled steel sheet. In order to reliably obtain this effect, the Cr content is preferably set to 0.020% or more. The Cr content is more preferably 0.050% or more, 0.100% or more, and even more preferably 0.200% or more.

[0120] On the other hand, if the Cr content exceeds 0.660%, the ductility of the hot-rolled steel sheet deteriorates. Therefore, the Cr content is set to 0.660% or less. The Cr content is preferably 0.500% or less, and more preferably 0.400% or less.

[0121] Mo: 0.001~0.300%

[0122] Mo is an element that increases the strength of a hot-rolled steel sheet by forming fine carbides in steel. In order to reliably obtain this effect, the Mo content is preferably set to 0.001% or more.

[0123] On the other hand, if the Mo content exceeds 0.300%, the ductility of the hot-rolled steel sheet deteriorates. Therefore, the Mo content is set to 0.300% or less.

[0124] Cu: 0.001~1.000%

[0125] Cu has the function of improving the hardenability of steel and precipitating as carbides in steel at low temperatures to improve the strength of hot-rolled steel sheets. In order to more reliably obtain the effects brought about by the above functions, the Cu content is preferably set to 0.001% or more.

[0126] However, when the Cu content exceeds 1.000%, grain boundary cracking of the slab may occur. Therefore, the Cu content is set to 1.000% or less.

[0127] Ni: 0.001~1.000%

[0128] Ni has the effect of improving the hardenability of the steel sheet and thus improving the strength of the hot-rolled steel sheet. In addition, Ni has the effect of effectively suppressing the grain boundary cracking of the slab caused by Cu when containing Cu. In order to more reliably obtain the effect brought about by the above-mentioned effect, it is preferred that the Ni content be set to 0.001% or more.

[0129] Ni is an expensive element, so it is not economically preferable to contain a large amount of Ni. Therefore, the Ni content is set to 1.000% or less.

[0130] Sn: 0.001~0.100%

[0131] Sn increases the strength of the hot-rolled steel sheet by dissolving in the steel, and also improves the ductility and hole expandability. In order to reliably exert this effect, the Sn content may be set to 0.001% or more.

[0132] On the other hand, if the Sn content exceeds 0.100%, grain boundary embrittlement cracking occurs during heat treatment. Therefore, the Sn content is set to 0.100% or less.

[0133] Ca: 0.0005~0.0200%

[0134] Ca has the function of improving the formability of the hot-rolled steel sheet by controlling the shape of inclusions to a preferred shape. In order to more reliably obtain the effect brought about by the above function, the Ca content is preferably set to 0.0005% or more.

[0135] On the other hand, if the Ca content exceeds 0.0200%, inclusions are excessively generated in the steel, deteriorating the ductility of the hot-rolled steel sheet. Therefore, the Ca content is set to 0.0200% or less.

[0136] As: 0.001~0.100%

[0137] As contributes to improving the hydrogen embrittlement resistance of the hot-rolled steel sheet by lowering the austenite single-phase transformation temperature and refining the prior austenite grains. In order to reliably obtain this effect, the As content is preferably set to 0.001% or more.

[0138] On the other hand, even if a large amount of As is contained, the above-mentioned effect is saturated, so the As content is made 0.100% or less.

[0139] Bi: 0.001~0.020%

[0140] Bi has the function of improving the formability of the hot-rolled steel sheet by refining the solidified structure. In order to more reliably obtain the effect of this function, the Bi content is preferably set to 0.001% or more.

[0141] On the other hand, even if the Bi content exceeds 0.020%, the effect due to the above-mentioned action is saturated, which is not economically preferable. Therefore, the Bi content is set to 0.020% or less.

[0142] Mg: 0.0005~0.0200%

[0143] Mg has the function of improving the formability of the hot-rolled steel sheet by controlling the shape of inclusions to a preferred shape. In order to more reliably obtain the effect brought about by the above function, the Mg content is preferably set to 0.0005% or more.

[0144] On the other hand, if the Mg content exceeds 0.0200%, inclusions are excessively generated in the steel, deteriorating the ductility of the hot-rolled steel sheet. Therefore, the Mg content is set to 0.0200% or less.

[0145] Zr: 0.001~0.400%

[0146] Zr is an element that contributes to inclusion control, particularly to fine dispersion of inclusions, thereby improving the strength of the hot-rolled steel sheet. In order to reliably obtain this effect, the Zr content is preferably set to 0.001% or more.

[0147] On the other hand, if Zr is contained in a large amount, the surface properties of the hot-rolled steel sheet may be significantly deteriorated. Therefore, the Zr content is set to 0.400% or less.

[0148] V: 0.001~0.200%

[0149] V is an element that increases the strength of a hot-rolled steel sheet by forming fine carbides in steel. In order to reliably obtain this effect, the V content is preferably set to 0.001% or more.

[0150] On the other hand, if the V content exceeds 0.200%, the hole expandability of the hot-rolled steel sheet deteriorates. Therefore, the V content is set to 0.200% or less.

[0151] REM: 0.0005~0.1000%

[0152] REM has the function of improving the formability of the hot-rolled steel sheet by controlling the shape of the inclusions to a preferred shape. In order to more reliably obtain the effect of the above function, the REM content is preferably set to 0.0005% or more.

[0153] On the other hand, if the REM content exceeds 0.1000%, inclusions are excessively generated in the steel, deteriorating the ductility of the hot-rolled steel sheet. Therefore, the REM content is set to 0.1000% or less.

[0154] Here, REM refers to a total of 17 rare earth elements including Sc, Y and lanthanoid elements, and the above-mentioned REM content refers to the total content of these elements. In the case of lanthanoid elements, they are added in the form of mixed rare earth metals in industry.

[0155] Co: 0.0005~0.2000%

[0156] Co is an element that contributes to inclusion control, particularly to fine dispersion of inclusions, thereby improving the strength of the hot-rolled steel sheet. In order to reliably obtain this effect, the Co content is preferably set to 0.0005% or more.

[0157] On the other hand, if a large amount of Co is contained, the surface properties of the hot-rolled steel sheet may be significantly deteriorated. Therefore, the Co content is set to 0.2000% or less.

[0158] W: 0.0005~0.2000%

[0159] W is an element that contributes to inclusion control, particularly to fine dispersion of inclusions, thereby improving the strength of the hot-rolled steel sheet. In order to reliably obtain this effect, the W content is preferably set to 0.0005% or more.

[0160] On the other hand, if a large amount of W is contained, the surface properties of the hot-rolled steel sheet may be significantly deteriorated. Therefore, the W content is set to 0.2000% or less.

[0161] Zn: 0.0005~0.2000%

[0162] Zn is an element that contributes to inclusion control, particularly to fine dispersion of inclusions, thereby improving the strength of the hot-rolled steel sheet. In order to reliably obtain this effect, the Zn content is preferably set to 0.0005% or more.

[0163] On the other hand, if Zn is contained in a large amount, the surface properties of the hot-rolled steel sheet may be significantly deteriorated. Therefore, the W content is set to 0.2000% or less.

[0164] The chemical composition of the hot-rolled steel sheet mentioned above can be analyzed using a spark discharge emission spectrometer or the like. It should be noted that C and S are values ​​identified by burning in an oxygen flow using a gas component analyzer or the like and measuring by infrared absorption method. In addition, N is a value identified by melting a test piece collected from a hot-rolled steel sheet in a helium flow and measuring by thermal conductivity method.

[0165] Next, the metal structure of the hot-rolled steel sheet according to the present embodiment will be described.

[0166] In the metal structure of the hot-rolled steel sheet according to the present embodiment, in terms of area %, bainite is 10% or more, tempered martensite is 10% or more, the total of bainite and tempered martensite is 70-96%, fresh martensite is 20% or less, retained austenite is 4-12%, ferrite is 5% or less, pearlite is 5% or less, the average grain size of prior austenite grains is 20.0 μm or less, the average aspect ratio of prior austenite grains is 3.00 or less, and the area ratio of the aggregate of fresh martensite and retained austenite having a major diameter of 30 μm or more is 5% or less.

[0167] In this embodiment, the metal structure at the 1 / 4 position of the hot rolled steel sheet thickness (the region from 1 / 8 to 3 / 8 of the thickness from the surface) is defined because the metal structure at this position represents a representative metal structure of the hot rolled steel sheet.

[0168] Each regulation is described below.

[0169] Bainite: more than 10%

[0170] Bainite is a structure that improves the ductility of hot-rolled steel sheets. If the area ratio of bainite is less than 10%, the desired ductility cannot be obtained in the hot-rolled steel sheets. Therefore, the area ratio of bainite is set to 10% or more. The area ratio of bainite is preferably 20% or more or 30% or more, and more preferably 40% or more.

[0171] The upper limit of the area ratio of bainite is not particularly limited, but may be set to 96% or less due to the relationship with the area ratio of retained austenite. The area ratio of bainite may also be set to 80% or less or 75% or less.

[0172] Tempered martensite: more than 10%

[0173] Tempered martensite is an effective structure for obtaining desired ductility, hole expansion and hydrogen embrittlement resistance in hot-rolled steel sheets. If the area ratio of tempered martensite is less than 10%, the desired ductility, hole expansion and hydrogen embrittlement resistance cannot be obtained in the hot-rolled steel sheets. Therefore, the area ratio of tempered martensite is set to 10% or more. The area ratio of tempered martensite is preferably 15% or more or 20% or more, and more preferably 30% or more.

[0174] The upper limit of the area ratio of tempered martensite is not particularly limited, but may be set to 96% or less due to the relationship with the area ratio of retained austenite. The area ratio of tempered martensite may be set to 80% or less, 60% or less, or 50% or less.

[0175] Total of bainite and tempered martensite: 70-96%

[0176] If the area ratio of bainite and tempered martensite is less than 70% in total, the desired ductility, hole expansion and / or hydrogen embrittlement resistance cannot be obtained in the hot-rolled steel sheet. Therefore, the area ratio of bainite and tempered martensite is set to a total of 70% or more. The area ratio of bainite and tempered martensite is preferably 75% or more, and more preferably 80% or more.

[0177] The upper limit of the total area ratio of bainite and tempered martensite is not particularly limited, but is set to 96% or less in relation to the area ratio of retained austenite. The total area ratio of bainite and tempered martensite may also be set to 90% or less.

[0178] New martensite: less than 20%

[0179] Fresh martensite is a structure that improves the strength of hot-rolled steel sheets, but it is also a structure that deteriorates the hole expandability and hydrogen embrittlement resistance. If the area ratio of fresh martensite exceeds 20%, the hole expandability and hydrogen embrittlement resistance of the hot-rolled steel sheet deteriorate. Therefore, the area ratio of fresh martensite is set to 20% or less. The area ratio of fresh martensite is preferably 15% or less, more preferably 10% or less, and even more preferably 7% or less.

[0180] The lower limit of the area ratio of fresh martensite is not particularly limited, but may be set to 0%.

[0181] Retained austenite: 4-12%

[0182] Retained austenite is a structure that improves the ductility of the hot-rolled steel sheet. If the area ratio of retained austenite is less than 4%, the desired ductility cannot be obtained in the hot-rolled steel sheet. Therefore, the area ratio of retained austenite is set to 4% or more. The area ratio of retained austenite is preferably 6% or more, and more preferably 7% or more.

[0183] On the other hand, if the area ratio of retained austenite exceeds 12%, the hole expandability of the hot-rolled steel sheet deteriorates. Therefore, the area ratio of retained austenite is set to 12% or less. The area ratio of retained austenite is preferably 10% or less.

[0184] Ferrite: less than 5%

[0185] If the area ratio of ferrite exceeds 5%, the strength of the hot-rolled steel sheet deteriorates. Therefore, the area ratio of ferrite is set to 5% or less. The area ratio of ferrite is preferably 3% or less, and more preferably 2% or less. The area ratio of ferrite may also be 0%.

[0186] Pearlite: less than 5%

[0187] If the area ratio of pearlite exceeds 5%, the strength of the hot-rolled steel sheet deteriorates. Therefore, the area ratio of pearlite is set to 5% or less.

[0188] The area ratio of pearlite is preferably 3% or less. By setting the area ratio of pearlite to 3% or less, the TS-E1 balance in the hot-rolled steel sheet can be further improved. That is, high strength and excellent ductility can be achieved at a higher level. The area ratio of pearlite is preferably small, so the area ratio of pearlite can also be set to 0%.

[0189] Hereinafter, the method for measuring the area ratio of each structure will be described.

[0190] Test specimens were collected from the hot-rolled steel plates in a cross section parallel to the rolling direction so that the metal structure at a position 1 / 4 of the plate thickness from the surface (the region from 1 / 8 of the depth of the plate thickness from the surface to 3 / 8 of the depth of the plate thickness from the surface) and at the center position in the plate width direction could be observed.

[0191] After the cross section of the above test piece is polished with #600 to #1500 silicon carbide paper, it is finished into a mirror surface using a liquid obtained by dispersing diamond powder with a particle size of 1 to 6 μm in a diluent such as alcohol or pure water. Next, the strain introduced into the surface layer of the sample is removed by polishing with colloidal silica that does not contain an alkaline solution at room temperature. At any position in the length direction of the sample cross section, an area with a length of 100 μm and a depth of 1 / 8 of the plate thickness from the surface to a depth of 3 / 8 of the plate thickness from the surface is set as an observation field (hereinafter referred to as an EBSD observation field), and the measurement is performed by electron backscatter diffraction at a measurement interval of 0.1 μm to obtain crystal orientation information.

[0192] For the measurement, an EBSD device consisting of a thermal field emission scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSD detector (DVC5 detector manufactured by TSL) was used. At this time, the vacuum degree in the EBSD device was set to 9.6×10 -5 Pa or less, the acceleration voltage is set to 15 kV, the irradiation current level is set to 13, and the electron beam irradiation level is set to 62. Based on the obtained crystal orientation information, the "Phase Map" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device is used to determine the area where the crystal structure is fcc, and calculate the area ratio of the area. Thus, the area ratio of retained austenite is obtained.

[0193] Next, the region with a crystal structure of bcc is judged as bainite, ferrite, pearlite, fresh martensite and tempered martensite. For these regions, the "Grain Orientation Spread" function carried in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device is used. Under the condition that the 15° grain boundary is regarded as the crystal grain boundary, the region with a "Grain Orientation Spread" of less than 1° is extracted as ferrite. The area ratio of the extracted ferrite is calculated to obtain the area ratio of ferrite.

[0194] Next, in the remaining region (region where "Grain Orientation Spread" exceeds 1°), under the condition that the 15° grain boundary is defined as the crystal grain boundary, when the maximum value of "Grain Average IQ" in the ferrite region is set to Iα, the region exceeding Iα / 2 is extracted as bainite, and the region below Iα / 2 is extracted as "pearlite, fresh martensite, and tempered martensite." The area ratio of the extracted bainite is calculated to obtain the area ratio of bainite.

[0195] The extracted “pearlite, new martensite, and tempered martensite” were distinguished from each other by the following method.

[0196] It should be noted that IQ sometimes changes depending on the state of the sample surface and the accuracy of the measurement. In order to eliminate these effects, it is sufficient to use a CI (Confidence Index) value of 0.8 or more, which shows the reliability of the crystal orientation information. When the CI value becomes less than 0.8, electrolytic polishing is performed again by the above method, and the working distance between the sample and the EBSD pattern detector is adjusted, the acceleration voltage and the irradiation current level are adjusted, or the gain or exposure of the detector is adjusted, and data is obtained in such a way that the CI value becomes 0.8 or more.

[0197] In order to observe the same area as the EBSD measurement area by SEM, a Vickers indentation is engraved near the observation position. Afterwards, the organization of the observation surface is retained, the contaminants on the surface are ground and removed, and nitric acid is etched. Next, the same field of view as the EBSD observation surface (EBSD observation field of view) is observed by SEM at a magnification of 3000 times. In the EBSD measurement, in the area judged as "pearlite, new martensite and tempered martensite", the area with the lower organization in the grain and the cementite precipitated in multiple variants is judged as tempered martensite. The area where cementite precipitates in lamellar form is judged as pearlite. The area with high brightness and no lower organization due to corrosion is judged as new martensite. By calculating the respective area ratios, the area ratios of tempered martensite, pearlite and new martensite are obtained.

[0198] Contaminants on the surface of the observation surface may be removed by lapping with aluminum oxide particles having a particle size of 0.1 μm or less or by Ar ion sputtering.

[0199] It should be noted that the rolling direction of the hot-rolled steel sheet can be determined by the following method.

[0200] First, a test piece is collected in such a way that the plate thickness section of the hot-rolled steel plate can be observed. The plate thickness section of the collected test piece is finished by mirror polishing and then observed using an optical microscope. The observation range is set to the full thickness of the plate, and the dark area is judged as an inclusion. Among the inclusions with a long axis length of 5μm or more, the direction parallel to the direction in which the inclusion extends is judged as the rolling direction.

[0201] The average grain size of the original austenite grains: 20.0 μm or less

[0202] If the grain size of the original austenite grains is large, the local elongation deteriorates, resulting in deterioration of the hole expandability of the hot-rolled steel sheet. If the average grain size of the original austenite grains exceeds 20.0 μm, the deterioration of the hole expandability of the hot-rolled steel sheet becomes significant. Therefore, the average grain size of the original austenite grains is set to 20.0 μm or less. The average grain size of the original austenite grains is preferably 15.0 μm or less, and more preferably 13.0 μm or less.

[0203] The smaller the average grain size of the prior austenite grains, the more the hole expandability of the hot-rolled steel sheet improves, but even if it is set to less than 7.0 μm, the effect is saturated. Therefore, the average grain size of the prior austenite grains may be set to 7.0 μm or more.

[0204] Average aspect ratio of prior austenite grains: 3.00 or less

[0205] If the average aspect ratio of the prior austenite grains exceeds 3.00, the hole expandability of the hot-rolled steel sheet deteriorates. Therefore, the average aspect ratio of the prior austenite grains is set to 3.00 or less. The average aspect ratio of the prior austenite grains is preferably 2.50 or less, more preferably 2.00 or less, and even more preferably 1.50 or less.

[0206] The aspect ratio of the prior austenite grains is the value obtained by dividing the major axis of the prior austenite grains by the minor axis, and takes a value greater than 1.00. The smaller the aspect ratio, the more equiaxed the grains are, and the larger the aspect ratio, the flatter the grains become.

[0207] Determination method of average grain size and average aspect ratio of prior austenite grains

[0208] The sample is collected in a cross section parallel to the rolling direction of the hot-rolled steel plate in such a way that a position 1 / 4 of the plate thickness can be observed from the surface (an area from 1 / 8 of the plate thickness to 3 / 8 of the plate thickness from the surface). The structure of the plate thickness cross section is revealed using a saturated aqueous solution of picric acid and a sodium dodecylbenzene sulfonate etching solution. For the position 1 / 4 of the plate thickness from the surface of the sample (an area from 1 / 8 of the plate thickness to 3 / 8 of the plate thickness from the surface), the grain size of the original austenite grains is measured by taking a metal structure photograph obtained by taking at least 3 EBSD observation fields at a magnification of 500 times. For one original austenite grain contained in each observation field, the equivalent circle diameter is calculated. The above operation is performed on all the original austenite grains contained in each observation field, excluding the original austenite grains that are not included in the shooting field as a whole, such as the ends of the shooting field, to obtain the equivalent circle diameter of all the original austenite grains in each shooting field. The average grain size of the prior austenite grains was obtained by calculating the average value of the circle-equivalent diameters of the prior austenite grains obtained in each imaging field of view.

[0209] In addition, when prior austenite grains having an equivalent circle diameter of less than 2.0 μm were included, the above-mentioned measurement was performed excluding these grains.

[0210] In addition, the major axis and minor axis of at least 20 original austenite grains with an equivalent circle diameter of 2.0 μm or more contained in each of the above-mentioned shooting fields are measured. The average major axis and the average minor axis of the original austenite grains are obtained by calculating the average value of the major axis and the minor axis obtained by measuring each original austenite grain. The average aspect ratio of the original austenite grains is obtained by calculating their ratio (average major axis / average minor axis).

[0211] Area ratio of aggregates of fresh martensite and retained austenite with a major diameter of 30 μm or more: 5% or less

[0212] If the area ratio of the aggregate of fresh martensite and retained austenite with a long diameter of 30 μm or more exceeds 5%, the hydrogen embrittlement resistance of the hot-rolled steel sheet, especially at the cut end surface, deteriorates. Therefore, the area ratio of the aggregate of fresh martensite and retained austenite with a long diameter of 30 μm or more is set to 5% or less. In order to further improve the hydrogen embrittlement resistance, the area ratio of the aggregate of fresh martensite and retained austenite with a long diameter of 30 μm or more is preferably set to 2% or less.

[0213] The lower the area ratio of the aggregate of fresh martensite and retained austenite having a major diameter of 30 μm or more, the better. Therefore, the area ratio of the aggregate of fresh martensite and retained austenite having a major diameter of 30 μm or more may be set to 0%.

[0214] The aggregate of fresh martensite and retained austenite will be described.

[0215] A certain fresh martensite or retained austenite is approximated as an ellipsoid (ellipsoid 1), and the fresh martensite or retained austenite close to the ellipsoid 1 is also approximated as an ellipsoid (ellipsoid 2). Next, the distance l between ellipsoid 1 and ellipsoid 2 is calculated. When the major diameter of ellipsoid 1 is set to a, when the distance l between ellipsoid 1 and ellipsoid 2 is less than 1.5×a, the ellipsoid 1 and the ellipsoid 2 close to ellipsoid 1 are regarded as one aggregate. The fresh martensite and retained austenite in the metal structure are approximated as ellipsoids, and the major diameter a of the ellipsoid and the distance l between the close ellipsoids are calculated. Based on the above criteria, the aggregate of fresh martensite and retained austenite is determined. The major diameter is calculated for the aggregate of the determined fresh martensite and retained austenite, and the area ratio of the aggregate with a major diameter of 30 μm or more is calculated, thereby obtaining the area ratio of the aggregate of fresh martensite and retained austenite with a major diameter of 30 μm or more.

[0216] In addition, the determination of fresh martensite and retained austenite is performed by the same method as the method of measuring the area ratio of the above-mentioned structure.

[0217] A method for approximating fresh martensite and retained austenite to ellipsoids will be described.

[0218] like Figure 1 As shown in FIG. , according to the area S of the region of the crystal grains not included in the ellipsoid out The area S of the non-crystalline region within the ellipsoid in The ellipsoid is approximated in such a way that the sum of is minimized. By approximating the ellipsoid in this way, x0, y0, a, and b are obtained.

[0219] The region where the average nanoindentation hardness at a load of 5000 μN and a load speed of 500 μN / s in bainite is 4.7 GPa or less: 30% or less

[0220] By reducing the area ratio of the low hardness region in bainite, the TS-E1 balance in the hot-rolled steel sheet can be further improved. That is, high strength and excellent ductility can be achieved at a higher level. Therefore, the region where the average value of the nanoindentation hardness is 4.7 GPa or less at a load of 5000 μN and a load speed of 500 μN / s in bainite can also be set to less than 30%.

[0221] A method for measuring the ratio (percentage) of regions where the average value of the nanoindentation hardness is 4.7 GPa or less at a load of 5000 μN and a load speed of 500 μN / s in bainite will be described.

[0222] Bainite is determined by the same method as the method for determining the area ratio of the above-mentioned organization. For all areas determined as bainite, the nanoindentation hardness is measured at a load of 5000μN and a load speed of 500μN / s. For an area determined as bainite, the nanoindentation hardness of at least 10 points is measured, and the average value of the nanoindentation hardness of the area is calculated. Next, the area ratio of the area where the average value of the nanoindentation hardness is below 4.7GPa is calculated. By dividing the area ratio of the area where the average value of the nanoindentation hardness is below 4.7GPa by the area ratio of bainite and multiplying by 100, the proportion (percentage) of the area where the average value of the nanoindentation hardness is below 4.7GPa at a load of 5000μN and a load speed of 500μN / s in bainite is obtained.

[0223] In addition, TriboScope / Tribo Indenter manufactured by Hysitron Corporation was used for the measurement.

[0224] Tensile strength: above 1100MPa

[0225] The tensile strength of the hot-rolled steel sheet of this embodiment may also be 1100 MPa or more. By setting the tensile strength to 1100 MPa or more, it can be suitably applied to various automotive running parts. The tensile strength may also be set to 1150 MPa or more, 1200 MPa or more, or 1300 MPa or more.

[0226] The higher the tensile strength, the more preferable it is, but it may be set to 1450 MPa or less.

[0227] Uniform elongation: more than 5.5%

[0228] The uniform elongation of the hot-rolled steel sheet of this embodiment may be 5.5% or more. By setting the uniform elongation to 5.5% or more, it can be suitably applied to automotive chassis parts. The uniform elongation is preferably 6.0% or more or 7.0% or more.

[0229] The upper limit is not particularly limited, but may be set to 20.0% or less.

[0230] The tensile strength and uniform elongation were measured by a tensile test using a No. 5 test piece of JIS Z 2241: 2011 in accordance with JIS Z 2241: 2011. The tensile test piece was collected at the center of the sheet width, with the direction perpendicular to the rolling direction being the longitudinal direction.

[0231] It should be noted that the uniform elongation is the “total elongation at the maximum test force” as defined in JIS Z 2241:2011.

[0232] Hole expansion rate: more than 30%

[0233] The hole expansion ratio of the hot-rolled steel sheet of this embodiment may also be 30% or more. By setting the hole expansion ratio to 30% or more, it can be suitably applied to automotive running parts. The hole expansion ratio is preferably 35% or more, 40% or more, or 45% or more. The upper limit is not particularly specified, but may be set to 70% or less.

[0234] The hole expansion ratio is measured by a hole expansion test in accordance with JIS Z 2256:2020.

[0235] Evaluation of hydrogen embrittlement resistance

[0236] The hydrogen embrittlement resistance of the hot-rolled steel sheet was evaluated by the following method.

[0237] A 50mm×50mm test piece was collected from the hot-rolled steel plate. A punch of φ10 mm and a die of φ10mm+0.2×plate thickness were used to form a punch hole in the center of the test piece. Next, the test piece was immersed in hydrochloric acid at pH 2, and the hydrogen embrittlement resistance was evaluated by whether cracks occurred on the cut end surface. Even if the test piece was immersed in hydrochloric acid for more than 72 hours, no cracks occurred on the cut end surface, which can be judged as excellent hydrogen embrittlement resistance. Furthermore, the test piece was immersed in hydrochloric acid under the same conditions, and the hydrochloric acid was replaced with new hydrochloric acid after 36 hours. Even if the test piece was immersed for a further 36 hours (a total of immersion for 72 hours), no cracks occurred on the cut section, which can be judged as having better hydrogen embrittlement resistance.

[0238] In addition, when the cut end surface was observed with an optical microscope and cracks exceeding 100 μm in length were observed, it was determined that cracks had occurred.

[0239] The hot rolled steel sheet of the present embodiment can also be made into surface treated steel sheet with coating on the surface for the purpose of improving corrosion resistance. The coating can be an electroplated layer or a hot dipped layer. As the electroplated layer, electrogalvanized layer, electroplated Zn-Ni alloy layer, etc. can be exemplified. As the hot dipped layer, hot dipped galvanized layer, alloyed hot dipped galvanized layer, hot dipped aluminum layer, hot dipped Zn-Al alloy layer, hot dipped Zn-Al-Mg alloy layer, hot dipped Zn-Al-Mg-Si alloy layer, etc. can be exemplified. The coating adhesion amount is not particularly limited and can be set to the same as in the past. In addition, after plating, suitable chemical conversion treatment (for example, coating and drying of the chromium-free chemical conversion treatment liquid of silicate system) is implemented to further improve corrosion resistance.

[0240] Next, a preferred method for producing the hot-rolled steel sheet according to the present embodiment will be described.

[0241] In addition, the temperature described below refers to the surface temperature of the slab or steel plate unless otherwise specified.

[0242] A preferred method for producing a hot-rolled steel sheet according to the present embodiment sequentially performs the following steps:

[0243] A heating step of maintaining the slab having the above chemical composition in a temperature range of 1220 to 1300° C. for more than 40 minutes;

[0244] A rough rolling step of performing rough rolling so that the first to third passes have a rolling reduction ratio of 10 to 30% and the fourth and subsequent passes have a rolling reduction ratio of 15 to 50%;

[0245] The final rolling process is a finishing rolling process performed at a temperature range of 940 to 1020°C and a reduction ratio of 25% or more;

[0246] After the finish rolling is completed, cooling begins within 2.0 seconds and cools to a temperature range of 300°C to (Ms-10)°C within 16.0 seconds;

[0247] After the cooling, the coiling step is performed in which coiling is started in the temperature range of 300°C to (Ms-10)°C and the retention time in the temperature range of 300 to 450°C after the start of coiling is 100 seconds or more.

[0248] In addition, in the said finishing rolling process, it is more preferable to perform the said finishing rolling so that the finishing rolling start temperature may become the temperature range of 1060-1080 degreeC.

[0249] In addition, in the coiling step, it is more preferable to perform the coiling so that the highest temperature after the start of the coiling becomes lower than 500°C.

[0250] Furthermore, in the cooling step and the coiling step, the cooling and the coiling are more preferably performed so that the total residence time in the temperature range of 450 to 500° C. becomes less than 2000 seconds.

[0251] Hereinafter, each step will be described.

[0252] Heating process

[0253] If the heating temperature is lower than 1220° C., solid solutionization does not proceed, the amount of ferrite increases, and the strength of the hot-rolled steel sheet deteriorates. Therefore, the heating temperature is preferably set to 1220° C. or higher. The heating temperature is more preferably 1240° C. or higher.

[0254] On the other hand, if the heating temperature exceeds 1300° C., the austenite grains coarsen during heating, resulting in deterioration of the hole expandability of the hot-rolled steel sheet. Therefore, the heating temperature is preferably set to 1300° C. or less. From the perspective of reducing energy costs, the heating temperature is preferably set to 1280° C. or less.

[0255] If the holding time in the temperature range of 1220-1300°C is less than 40 minutes, the solid solutionization does not progress, the amount of ferrite increases, and the strength of the hot-rolled steel sheet deteriorates. Therefore, the holding time in the above temperature range is preferably set to 40 minutes or more. The holding time is more preferably 60 minutes or more, and even more preferably 80 minutes or more.

[0256] The upper limit of the retention time is not particularly limited, but may be set to 200 minutes or less.

[0257] It should be noted that the slab to be heated is not particularly limited except that it has the above-mentioned chemical composition. For example, a slab produced by continuous casting by melting molten steel having the above-mentioned chemical composition in a converter or an electric furnace can be used. In place of the continuous casting method, an ingot casting method, a thin slab casting method, etc. can also be used.

[0258] Rough rolling process

[0259] If rolling is performed at a reduction rate of less than 10% in the first to third passes, or rolling is performed at a reduction rate of less than 15% in the fourth pass and thereafter, the prior austenite grains are coarsened. Therefore, it is preferred that each reduction rate in the first to third passes is set to 10% or more, and each reduction rate in the fourth pass and thereafter is set to 15% or more. It is more preferred that each reduction rate in the first to third passes is 15% or more or 20% or more, and each reduction rate in the fourth pass and thereafter is 20% or more or 25% or more.

[0260] In addition, if rolling with a reduction rate exceeding 30% is performed in the 1st to 3rd passes, or rolling with a reduction rate exceeding 50% is performed after the 4th pass, the finish rolling is performed in a state where the original austenite grains are uneven, and it becomes easy to form original austenite grains extending in a specific direction after the finish rolling. As a result, the average aspect ratio of the original austenite grains becomes higher, and the area ratio of the aggregate of the newly formed martensite and the retained austenite with a long diameter of more than 30 μm becomes higher. Therefore, it is preferred that each reduction rate of the 1st to 3rd passes is set to 30% or less, and each reduction rate after the 4th pass is set to 50% or less. It is more preferred that each reduction rate of the 1st to 3rd passes is 25% or less, and each reduction rate after the 4th pass is 40% or less.

[0261] It should be noted that the reduction ratio of each pass can be expressed by {1-(t1 / t0)}×100(%) when the inlet thickness of each pass is set to t0 and the outlet thickness of each pass is set to t1.

[0262] The rough rolling finishing temperature (the exit temperature of the final pass of rough rolling) is not particularly limited, but is preferably 1070° C. or higher from the viewpoint of thermal deformation resistance and preferably 1200° C. or lower from the viewpoint of reducing scratches caused by scale bite.

[0263] Finishing process

[0264] In the finishing process, if the rolling temperature or reduction ratio in the final pass is too low, recrystallization does not progress sufficiently, and the average grain size of the original austenite grains, the average aspect ratio of the original austenite grains, and / or the area ratio of the aggregate of the newly formed martensite and the retained austenite with a long diameter of 30 μm or more cannot be preferably controlled. Therefore, in the finishing process, it is preferred to perform the final pass rolling in a temperature range of 940° C. or more and at a reduction ratio of 25% or more.

[0265] The final rolling is preferably performed at 960°C or higher, more preferably at 1010°C or lower, and more preferably at a reduction ratio of 30% or higher. The final rolling reduction ratio may be set to 50% or lower.

[0266] In addition, in the finishing step, it is more preferable to perform finishing rolling in a manner such that the finishing rolling start temperature (entry side temperature of the first stage of finishing rolling) is in a temperature range of 1060 to 1080°C. By setting the finishing rolling start temperature to a temperature range of 1060 to 1080°C, the area ratio of the aggregate of fresh martensite and retained austenite having a long diameter of 30 μm or more can be further reduced. As a result, a hot-rolled steel sheet having a more excellent hydrogen embrittlement resistance can be manufactured.

[0267] Cooling process

[0268] If the time from the completion of the finish rolling to the start of cooling exceeds 2.0 seconds, the grain growth of the austenite recrystallized grains progresses, resulting in the coarsening of the prior austenite grains. Therefore, after the completion of the finish rolling, it is preferred to start cooling within 2.0 seconds.

[0269] The cooling mentioned here does not include air cooling, and the time until the start of cooling refers to the time from the rolling of the final pass of the finish rolling to the start of water cooling.

[0270] Cooling can also be started immediately after finishing rolling, but it becomes necessary to spray cooling water directly below the finishing mill, and the rolls are overcooled, making it difficult to control the final rolling temperature. Therefore, the time until the start of cooling is more preferably set to 1.0 second or more.

[0271] If the cooling time from the completion of finish rolling to the temperature range of 300°C to (Ms-10)°C exceeds 16.0 seconds, ferrite is excessively generated. Therefore, after the start of cooling, it is preferred to cool to the temperature range of 300°C to (Ms-10)°C within 16.0 seconds after the completion of finish rolling. The shorter the cooling time, the better, but in order to cool to the desired temperature range in a short time, it is necessary to increase the mass density, increase the load on the cooling nozzle, and thus damage the economy. Therefore, the cooling time to the temperature range of 300°C to (Ms-10)°C is more preferably set to more than 5.0 seconds or more than 7.0 seconds from the completion of finish rolling.

[0272] After cooling to a temperature range of 300°C to (Ms-10)°C, cooling is stopped. If the cooling stop temperature is lower than 300°C, bainite is excessively generated. Therefore, the cooling stop temperature is set to 300°C or higher. The cooling stop temperature is preferably 320°C or higher.

[0273] On the other hand, if the cooling stop temperature exceeds Ms-10° C., the amount of bainite and tempered martensite decreases. Therefore, the cooling stop temperature is preferably set to Ms-10° C. or less. The cooling stop temperature is more preferably 400° C. or less.

[0274] The steel sheet is immediately wound into a coil after the cooling is stopped. That is, the winding temperature is the same as the cooling stop temperature.

[0275] It should be noted that Ms (°C) can be obtained by the following formula.

[0276] Ms=496×(1-0.62×C)×(1-0.0092×Mn)×(1-0.033×Si)×(1-0.045×Ni)×(1-0.07×Cr)×(1-0.029×Mo)×(1-0.018×W)×(1+0.012×Co)

[0277] Coiling process

[0278] After the start of coiling, when the hot-rolled steel sheet is gradually coiled into a coil, the temperature of the steel sheet rises due to the heat caused by phase transformation. In particular, the temperature is likely to rise in the center of the coil or the center of the outermost peripheral surface of the coil in the plate width direction. After the start of coiling, by fully ensuring the residence time in the temperature range of 300 to 450°C, the area ratio of the aggregate of fresh martensite and retained austenite with a long diameter of more than 30 μm can be reduced. If the residence time in the temperature range of 300 to 450°C after the start of coiling is less than 100 seconds, the area ratio of the aggregate of fresh martensite and retained austenite with a long diameter of more than 30 μm cannot be reduced. Therefore, the residence time in the temperature range of 300 to 450°C after the start of coiling is preferably set to more than 100 seconds.

[0279] It should be noted that the temperature referred to here is the surface temperature of the center portion in the sheet width direction of the outermost peripheral surface of the coil.

[0280] The residence time in the temperature range of 300 to 450°C refers to the time from when coiling starts after cooling to the temperature range of 300°C to (Ms-10)°C until the temperature drops to 300°C, or until the temperature rises to 450°C due to heat generation caused by phase transformation.

[0281] Even if the temperature rises to over 450°C due to heat generation caused by phase change after the start of coiling and then drops to the temperature range of 300 to 450°C, the time when the temperature temporarily rises to over 450°C is not added to the residence time.

[0282] In the coiling process, it is more preferable to coil the steel sheet so that the maximum temperature after the start of coiling becomes lower than 500°C. After the start of coiling, the temperature rise caused by reflux heat exchange is controlled so that the surface temperature of the central part in the sheet width direction of the outermost peripheral surface of the coil becomes lower than 500°C, so that the amount of pearlite can be further reduced. As a result, the TS-E1 balance in the hot-rolled steel sheet can be further improved. That is, high strength and excellent ductility can be achieved at a higher level.

[0283] In the cooling process and the coiling process, it is more preferable to cool and coil the steel sheet in such a way that the total residence time in the temperature range of 450 to 500°C becomes less than 2000 seconds. By cooling and coiling the steel sheet in such a way that the total residence time in the temperature range of 450 to 500°C becomes less than 2000 seconds, the area ratio of the region with low hardness in the bainite can be reduced. Thus, the TS-El balance in the hot-rolled steel sheet can be further improved. That is, high strength and excellent ductility can be achieved at a higher level.

[0284] The total residence time here refers to the total residence time in the temperature range of 450 to 500° C. during cooling and the residence time in the temperature range of 450 to 500° C. when the temperature rises due to heat generation caused by phase transformation after the start of coiling.

[0285] The hot-rolled steel sheet according to the present embodiment can be stably manufactured by the manufacturing method including the steps described above.

[0286] Example

[0287] Next, the embodiment of the present invention is described, but the conditions in the embodiment are a conditional example adopted to confirm the feasibility and effect of the present invention. The present invention is not limited to this conditional example. As long as the purpose of the present invention is achieved without departing from the gist of the present invention, the present invention can adopt various conditions.

[0288] By carrying out continuous casting, slabs having the chemical compositions shown in Tables 1A to 2B were obtained. Since cracks were observed in the slabs of Steel Nos. I, L, U, and Z during casting, the production was stopped at that point.

[0289] Next, coils made of hot-rolled steel sheets were produced under the conditions shown in Tables 3A to 4C.

[0290] In addition, in Test No. 5, since the deformation resistance during hot state was high, the production after the finish rolling was stopped.

[0291] From the outermost periphery of the obtained coil, a test piece was cut out for metal structure observation, tensile test, hole expansion test, and hydrogen embrittlement resistance evaluation. Each test method was the same as the above-mentioned method.

[0292] Furthermore, the metal structure of the obtained test piece was observed by the above-mentioned method. The obtained results are shown in Tables 5A to 5D.

[0293] It should be noted that each item in Table 5A to Table 5D represents the following contents.

[0294] B: Bainite

[0295] TM: Tempered Martensite

[0296] FM: Freshly formed martensite

[0297] γr: Retained austenite

[0298] α: Ferrite

[0299] P: Pearlite

[0300] Average grain size of original γ grains: Average grain size of original austenite grains

[0301] Average aspect ratio of original γ grains: Average aspect ratio of original austenite grains

[0302] In addition, for the "Area ratio of aggregates of FM and γr" in the table, when the area ratio of aggregates of fresh martensite and retained austenite with a major diameter of 30 μm or more exceeds 2% and is 5% or less, it is recorded as "B", when it is 2% or less, it is recorded as "A", and when it exceeds 5%, it is recorded as "C". Here, "A" and "B" are judged as passing, and "C" is judged as failing.

[0303] In addition, when the average value of the nanoindentation hardness at a load of 5000 μN and a load speed of 500 μN / s in bainite is 4.7 GPa or less for 30% or less, "OK" is recorded in "The area below 4.7 GPa is 30% or less", and when this condition is not met, it is recorded as "NG".

[0304] When the tensile strength is 1100 MPa or more, the hot-rolled steel sheet is judged as having high strength and is passed. On the other hand, when the tensile strength is less than 1100 MPa, the hot-rolled steel sheet is judged as not having high strength and is unqualified.

[0305] When the uniform elongation is 5.5% or more, the hot-rolled steel sheet is judged as acceptable as having excellent ductility. On the other hand, when the uniform elongation is less than 5.5%, the hot-rolled steel sheet is judged as unacceptable as having poor ductility.

[0306] When the hole expansion ratio is 30% or more, the hot rolled steel sheet is judged as having excellent hole expandability and is qualified. On the other hand, when the hole expansion ratio is less than 30%, the hot rolled steel sheet is judged as not having excellent hole expandability and is unqualified.

[0307] In the evaluation of hydrogen embrittlement resistance, when no cracks were generated on the cut end surface after the test piece was immersed in hydrochloric acid for more than 72 hours, it was determined to be qualified as a hot-rolled steel sheet having excellent hydrogen embrittlement resistance, and recorded as "B" in the table. On the other hand, when cracks were generated on the cut end surface after the test piece was immersed in hydrochloric acid for more than 72 hours, it was determined to be unqualified as a hot-rolled steel sheet not having excellent hydrogen embrittlement resistance, and recorded as "C" in the table.

[0308] Furthermore, the test piece was immersed in hydrochloric acid under the same conditions, and the hydrochloric acid was replaced with new hydrochloric acid after 36 hours. Even if the test piece was immersed for a further 36 hours (a total of immersion for 72 hours), no cracks occurred in the cut section. It was judged to be a hot-rolled steel plate with better hydrogen embrittlement resistance and recorded as "A" in the table.

[0309]

[0310]

[0311]

[0312]

[0313] [Table 3A]

[0314]

[0315] The underlined elements are outside the scope of the present invention or the production conditions are not preferred.

[0316] [Table 3B]

[0317]

[0318] The underlined elements are outside the scope of the present invention or the production conditions are not preferred.

[0319] [Table 3C]

[0320]

[0321] [Table 4A]

[0322]

[0323] The underlined elements are outside the scope of the present invention or the production conditions are not preferred.

[0324] [Table 4B]

[0325]

[0326] The crossed lines indicate that the products are outside the scope of the present invention or the production conditions are not preferred.

[0327] [Table 4C]

[0328]

[0329]

[0330]

[0331]

[0332]

[0333] As shown in Tables 5A to 5D, it is understood that the hot-rolled steel sheets of the examples of the present invention have high strength and excellent ductility, hole expandability, and hydrogen embrittlement resistance.

[0334] On the other hand, it is found that the hot-rolled steel sheets of the comparative examples are inferior in one or more of the above-mentioned characteristics.

[0335] Industrial Applicability

[0336] According to the above aspects of the present invention, it is possible to provide a hot-rolled steel sheet having high strength and excellent ductility, hole expandability, and hydrogen embrittlement resistance.

Claims

1. A hot rolled steel plate, It is characterized in that The chemical composition contains, by mass%, C: 0.13-0.23%, Si: 0.70-1.79%, Mn: 1.79-3.00%, P: 0.060% or less, S: 0.005% or less, N: 0.0070% or less, O: 0.010% or less, Al:0.010~0.430%、 Ti: 0.006~0.055%, Nb: 0.005-0.040%, B:0.0001~0.0030%、 Cr:0~0.660%、 Mo: 0~0.300%, Cu: 0~1.000%, Ni: 0~1.000%, Sn: 0~0.100%, Ca: 0~0.0200%, As: 0~0.100%, Bi: 0~0.020%, Mg: 0~0.0200%, Zr:0~0.400%、 V:0~0.200%、 REM: 0~0.1000%、 Co: 0~0.2000%, W: 0~0.2000% and Zn: 0~0.2000%, The rest contains Fe and impurities. In metal structures, expressed as area %, Bainite: more than 10%, Tempered martensite: more than 10%, Total of bainite and tempered martensite: 70-96%, New martensite: less than 20%, Retained austenite: 4-12%, Ferrite: less than 5%, Pearlite: less than 5%, The average grain size of the original austenite grains: 20.0 μm or less, The average aspect ratio of the original austenite grains: less than 3.00, The area ratio of the aggregate of fresh martensite and retained austenite having a major diameter of 30 μm or more is 5% or less.

2. The hot rolled steel sheet according to claim 1, It is characterized in that In the metal structure, The pearlite: less than 3%.

3. The hot rolled steel sheet according to claim 1 or 2, It is characterized in that The area of ​​the bainite where the average value of the nanoindentation hardness at a load of 5000 μN and a load speed of 500 μN / s is 4.7 GPa or less is 30% or less.

4. The hot rolled steel sheet according to claim 1 or 2, It is characterized in that The chemical composition contains, in mass%, one or more of the following elements: Cr:0.020~0.660%、 Mo: 0.001~0.300%, Cu: 0.001~1.000%, Ni: 0.001~1.000%, Sn: 0.001~0.100%, Ca: 0.0005~0.0200%, As: 0.001~0.100%, Bi: 0.001~0.020%, Mg: 0.0005~0.0200%, Zr:0.001~0.400%、 V:0.001~0.200%、 REM: 0.0005~0.1000%、 Co: 0.0005~0.2000%, W: 0.0005~0.2000% and Zn: 0.0005~0.2000%.

5. The hot rolled steel sheet according to claim 3, It is characterized in that The chemical composition contains, in mass%, one or more of the following elements: Cr:0.020~0.660%、 Mo: 0.001~0.300%, Cu: 0.001~1.000%, Ni: 0.001~1.000%, Sn: 0.001~0.100%, Ca: 0.0005 to 0.0200%, As: 0.001 to 0.100%, Bi: 0.001 to 0.020%, Mg: 0.0005 to 0.0200%, Zr:0.001~0.400%、 V:0.001~0.200%、 REM: 0.0005 to 0.1000%, Co: 0.0005 to 0.2000%, W: 0.0005 to 0.2000% and Zn: 0.0005 to 0.2000%.